Stakeholder Analysis of Indonesia's Trade the Regional Comprehensive Economic Partnership (RCEP) Actor Non-ASEAN - Ady Muzwardi; Mahadiansar Mahadiansar (Center for Maritime Policy and Governance Studies. Universitas Maritim Raja Ali Haji. Indonesia, 2024)
This study examines Indonesia’s trade relations with non-ASEAN member countries under the Regional Comprehensive Economic Partnership (RCEP). The RCEP, signed in 2020, presents Indonesia with significant opportunities to expand market access, particularly with key partners like China, Japan, South Korea, Australia, and New Zealand. However, challenges persist, particularly in terms of trade imbalances and competitive pressures. The research employs a mixed-methods approach, combining quantitative data from trade flow statistics and tariff reductions with qualitative insights from interviews and focus group discussions with key stakeholders. The Importance Performance Analysis (IPA) method was applied to assess the effectiveness of RCEP provisions. Results show that while Indonesia benefits from improved market access, significant trade deficits remain, especially with China and Australia. Stakeholders, including government agencies and private sector exporters, play pivotal roles in mitigating these challenges by addressing non-tariff barriers and enhancing trade facilitation. In conclusion, Indonesia must strategically leverage the RCEP framework to address trade imbalances and improve export competitiveness. Policy recommendations include enhancing stakeholder collaboration, improving infrastructure, and increasing awareness among small and medium enterprises (SMEs) to fully utilize RCEP benefits. These efforts will ensure Indonesia remains competitive in global trade.